Effect of chill cooling conditions on cooling rate, microstructure and casting/chill interfacial heat transfer coefficient for sand cast A319 alloy. (October 2014) - Farhang Mehr, F.; Reilly, C.; Cockcroft, S.; Maijer, D.; MacKay, R.
<x content-type="archive" xml:space="preserve">Abstract</x> A combination of experiments and numerical analyses were used to examine the cooling conditions, solidification microstructure and interfacial heat transfer in A319 cast in a chilled wedge format. Both solid copper chills and water cooled chills, with and without a delay in water cooling, were examined in the study. Various chill preheats were also included. The goal of the investigation is to explore methods of limiting heat transfer during solidification directly beside the chill and increasing cooling rates during solidification away from the chill. Within the range of conditions examined in the study, chill preheat was found to have only a small effect on cooling rates between 5 and 50 mm from the chill/casting interface, pour superheat a moderate effect and water cooling a significant effect. In comparison to the results for the solid chill, the solidification time at 5 mm with water cooling applied at the beginning of mould filling is reduced from 56 to 15 s and at 50 mm from 588 to 93·5 s. Furthermore, the average cooling rate during solidification is increased from 1·9 to 7·06°C s−1 at 5 mm and from 0·18 to 1·13°C s−1 at 50 mm. At 50 mm, for example, the increased cooling rate achieved with water translates into a reduction in secondary dendrite arm spacing from 40 to 25 μm or ∼40%. Delaying the water cooling by 10 s facilitated slow cooling rates at 5 mm (similar to those achieved with a solid chill) and high cooling rates 50 mm from the chill. A temperature based correlation was found to be suitable for characterising the behaviour of the interfacial heat transfer coefficient in the solid shill castings, whereas a time based correlation was needed for the water cooled castings.